Freeze-thaw and solvent-exchange strategy to generate physically cross-linked organogels and hydrogels of curdlan with tunable mechanical properties. (15th February 2022) - Wu, Min; Chen, Xiaoxia; Xu, Jiatong; Zhang, Hongbin
Abstract: Physical gels from natural polysaccharides present the advantage of no toxic cross-linking agents and no chemical modification during preparation. Herein, novel physical gels, transparent organogels and opaque hydrogels from the microorganism-derived (1, 3)- β -D-glucan of curdlan were prepared in dimethyl sulfoxide (DMSO) using the freeze-thaw technique, followed by a solvent-exchange strategy with water. The mechanical and structural properties of these gels were investigated by rheology, scanning electron microscopy, attenuated total reflection infrared spectroscopy, wide-angle X-ray diffraction and small-angle X-ray scattering. Gelation mechanisms and intermolecular interaction models have also been proposed. The good solvent DMSO serves as both a crosslinker and a pore-foaming agent in organogels. The reversible macromolecular conformation changes and phase separation of curdlan endow the gels with reversible transparency, volume change and tunable mechanical strength. The new design strategy of facile preparation and performance tuning provides a platform for developing new organogels and sterile hydrogels of curdlan. Graphical abstract: Unlabelled Image Highlights: A novel strategy to generate physically cross-linked curdlan gels was proposed. DMSO was first used as solvent and cryogen in preparing polysaccharide-cryogel. Curdlan organo/hydrogels were fabricated via freeze-thaw and solvent exchange processes. Gels present reversible transparency, volume change, and tunable mechanical strength. Gelation mechanisms and conformation changes were proposed at a molecular level.